Epäonnistumisen anatomia Kuvaputkitehdas Valcon nousu ja tuho 1976-1980 - Nevalainen, Pasi (Historiallinen arkisto, 2022)
Valco (1976-1980) was a state-owned company that manufactured cathode ray tubes for the television industry. The company's scandalous failure has been widely identified as one of the largest investment errors in Finland's economic history. This book is the first in-depth study of the roots, events, and consequences of that project. This study analyses Valco from a microhistorical perspective, looking at the numerous factors that led to its failure, from the company's founding process to investigations after its demise. These events are linked to broader phenomena in economic and business history, such as the changing economic policy of the government and the emergence of global supply chains in the electronics industry. Valco is a significant single case with a concrete impact on Finland's economic history. First, it changed the general perception of state-owned companies and, because of this, also more general perceptions of the role of the state in the economy. As a result, the initiative to develop the electronics industry was transferred to private companies such as Nokia. Second, Valco's case revealed the problems of state ownership of companies in a very concrete way. Due to Valco's failure, the objectives of state ownership were clarified, and the corporate governance system was modernised. In this way, Valco is linked to the modernization of Finnish state capitalism from the 1970s onwards.